2013
DOI: 10.1021/la3046498
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Agglomeration Control of LiMnPO4 Micro- and Nanocrystals

Abstract: Microwave-assisted hydrothermal synthesis was used to grow LiMnPO 4 micro-and nanocrystals from acetate precursors. By appropriate adjustment of the precursor concentration and the pH-value of the reactant, the product composition and purity along with the crystal size can be manipulated, resulting in particle-dimensions from around 10 µm down to a few 100 nm. Prisms and plates with hexagonal basal face as well as cuboid and rod-like particles were produced. The effects on the crystal morphology as well as on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Electrochemical studies were carried out using Swagelok-type cells. 42 Both the pure MoS 2 assembly and the C@MoS 2 @C hollow spheres electrodes were prepared from a mixture of the active material, carbon black (SuperP, Timcal) and polyvinylidene fluoride (PVDF, Sigma-Aldrich, 99%) binder with a weight ratio of 7:2:1, soaked in anhydrous 1methyl-2-pyrrolidinone (NMP, Sigma-Aldrich, 99%). The slurry was pasted on a circular Cu plate (approx.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Electrochemical studies were carried out using Swagelok-type cells. 42 Both the pure MoS 2 assembly and the C@MoS 2 @C hollow spheres electrodes were prepared from a mixture of the active material, carbon black (SuperP, Timcal) and polyvinylidene fluoride (PVDF, Sigma-Aldrich, 99%) binder with a weight ratio of 7:2:1, soaked in anhydrous 1methyl-2-pyrrolidinone (NMP, Sigma-Aldrich, 99%). The slurry was pasted on a circular Cu plate (approx.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A lot of experiments have demonstrated that the hydrothermal route is an effective approach for the synthesis of inorganic functional nanostructures with different morphologies. For example, Neef et al 19 achieved cuboid and rod-like LiMnPO 4 nanocrystals from acetate precursors via a microwave-assisted hydrothermal route. The preferential adsorption of PVA on (100) and (010) planes results in the orientation growth of PZT along the [001] directions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reaction time of the microwave-assisted solvothermal method described in this work is only 5 min, greatly reducing the reaction time. On the other hand, the electrochemical properties of LiMnPO 4 /C prepared in this work are better than those of samples prepared by MH reported in the literature [36][37][38][39]. The good electrochemical performance of LiMnPO 4 /C is due to the synergistic effect of flaky LiMnPO 4 and its carbon coating.…”
Section: Resultsmentioning
confidence: 46%
“…Ji et al [38] applied MH to prepare LiMnPO 4 , which delivered a capacity of 89.0 mAhÁg À1 at 0.05C. Neef et al [39] synthesized 100 nm LiMnPO 4 by MH, but they did not report its electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%